"n Pastoraatsperspektief op dreigende werksverlies - Schoeman, Roelf (HTS teologiese studies, 2008)
A pastoral perspective on the threatening loss of employment The changing employment situation in South Africa is currently characterized by the various challenges it poses to individuals in the workplace, such as affirmative action, voluntary severance packages and discharges. Discharges are often associated with employment insecurity and the threatening loss of employment. A psychological approach to the threatening loss of employment is on its own inadequate. The aim of this article is to investigate the possibilities of a holistic approach as part of pastoral support to persons experiencing the threat of losing their employment. It aims to argue that pastoral care can benefit from a multi- disciplinary approach to the threatening loss of employment. However, pastoral care needs guidelines to facilitate its relationship with psychology and to assist in dealing with faith in the counselling process. This article makes use of Gerkin’s model for pastoral care in order to provide some guidelines for pastoral care for individuals who are experiencing a protracted threat of loss of employment. Gerkin’s model will be brought into dialogue with a cognitive behavioural therapeutic model.